Electrical Stimulation Mapping of Brain Function: A Comparison of Subdural Electrodes and Stereo-EEG - Grande, Krista M.; Ihnen, Sarah K. Z.; Arya, Ravindra (Frontiers in Human Neuroscience, 2020)
Despite technological and interpretative advances, the non-invasive modalities used for pre-surgical evaluation of patients with drug-resistant epilepsy (DRE), fail to generate a concordant anatomo-electroclinical hypothesis for the location of the seizure onset zone in many patients. This requires chronic monitoring with intracranial electroencephalography (EEG), which facilitates better localization of the seizure onset zone, and allows evaluation of the functional significance of cortical regions-of-interest by electrical stimulation mapping (ESM). There are two principal modalities for intracranial EEG, namely subdural electrodes and stereotactic depth electrodes (stereo-EEG). Although ESM is considered the gold standard for functional mapping with subdural electrodes, there have been concerns about its utility with stereo-EEG. This is mainly because subdural electrodes allow contiguous sampling of the dorsolateral convexity of cerebral hemispheres, and permit delineation of the extent of eloquent functional areas on the cortical surface. Stereo-EEG, while having relatively sparse sampling on the cortical surface, offers the ability to access the depth of sulci, mesial and basal surfaces of cerebral hemispheres, and deep structures such as the insula, which are largely inaccessible to subdural electrodes. As stereo-EEG is increasingly the preferred modality for intracranial monitoring, we find it opportune to summarize the literature for ESM with stereo-EEG in this narrative review. Emerging evidence shows that ESM for defining functional neuroanatomy is feasible with stereo-EEG, but probably requires a different approach for interpretation and clinical decision making compared to ESM with subdural electrodes. We have also compared ESM with stereo-EEG and subdural electrodes, for current thresholds required to evoke desired functional responses vs. unwanted after-discharges. In this regard, there is preliminary evidence that ESM with stereo-EEG may be safer than ESM with subdural grids. Finally, we have highlighted important unanswered clinical and scientific questions for ESM with stereo-EEG in the hope to encourage future research and collaborative efforts.